2021
DOI: 10.1039/d1gc00721a
|View full text |Cite
|
Sign up to set email alerts
|

Production of HMF, FDCA and their derived products: a review of life cycle assessment (LCA) and techno-economic analysis (TEA) studies

Abstract: This review article summarises and discusses methodological and chemical aspects of LCA and TEA studies of HMF, FDCA and their derived products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 94 publications
1
90
0
1
Order By: Relevance
“…A study of FNR showed that the material prices of biobased and biodegradable plastic goods are 2–3 times higher than that of competing petrochemical materials (Rohstoffe eV FN, 2014). This is aligned with our findings of a HMF market price of approximately 2–3 EUR/kg compared to the fossil equivalent for polyester production of 0.85 EUR/kg para‐xylene (Davidson et al, 2021). To enter the market rapidly HMF must be converted into customer goods with advanced functionalities such as polyethylenefuranoate PEF, which has better barrier properties compared to PET (Burgess et al, 2014).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…A study of FNR showed that the material prices of biobased and biodegradable plastic goods are 2–3 times higher than that of competing petrochemical materials (Rohstoffe eV FN, 2014). This is aligned with our findings of a HMF market price of approximately 2–3 EUR/kg compared to the fossil equivalent for polyester production of 0.85 EUR/kg para‐xylene (Davidson et al, 2021). To enter the market rapidly HMF must be converted into customer goods with advanced functionalities such as polyethylenefuranoate PEF, which has better barrier properties compared to PET (Burgess et al, 2014).…”
Section: Resultssupporting
confidence: 92%
“…In its configuration of a sucrose HMF plant, Steinbach assumes production costs of 4.30 EUR/kg (Steinbach, 2020). Regardless of the underlying technology maturity, starting biomass, reaction media and calculation methods used, Davidson et al (2021) show HMF prices ranging from 0.35 (minimum production costs, not price) to 2.16 (minimum selling price) $/kg in a review article published in 2020. With prices between 2.21 and 2.90 EUR/kg, we are just out of the range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19–21 More importantly, 2-vinylfuran is an ideal substitute for styrene, and can be used to produce renewable polymers because its structure is similar to that of styrene, which is boosted by the success in manufacturing commercial biopolyesters using 2,5-furandicarboxylic acid to replace terephthalic acid. 22–26 Current methods for 2-vinylfuran synthesis are dominated by Peterson olefination, in which renewable furfural and (trimethylsilyl)methylmagnesium chloride (TMSCH 2 MgCl) are used. 27,28 The Wittig reaction has also been applied for this route, which affords a 99% yield of 2-vinylfuran when a methyltriphenylphosphonium methylcarbonate salt ([Ph 3 PCH 3 ][CH 3 OCO 2 ]) was employed.…”
Section: Introductionmentioning
confidence: 99%
“…The tremendous growth in the chemical manufacturing industry during the past century has relied heavily on exploiting fossil resources to provide both carbon for the chemicals and materials as well as energy for the processes. The chemical manufacturing contributes nearly 20% of the global greenhouse gas emissions (amounting to 880 Mt CO 2 equivalent in 2018) [1,2]. Replacing fossil energy with a renewable alternative such as solar energy and using biomass for providing renewable carbon provides a sustainable route for a fossil-free chemical industry of the future [3][4][5].…”
Section: Introductionmentioning
confidence: 99%